PERAN PENDIDIKAN TARI PUTRI KLASIK GAYA YOGYAKARTA BAGI PEREMPUAN JAWA, DULU DAN KINI - Tati Narawati (Humaniora, 2009)
This paper is a research report concerning Rama Sas, one of the great classical master dancers and choreographers of the court of Yogyakarta. As a boy, he had to master the female dancing because of the court rule that women of the aristocrat cannot appear in public in a wayang wong dance drama production. So because of his beautiful face, slender body, and delicate appearance, Rama Sas became a court dancer specializing in female characters. Women of the aristocrat concentrated on bedhaya and srimpi female dances. Due to the court restriction, women of the aristocrat were not allowed to move and act freely like men. This is a problem of gender of course. Rama Sas knew this problem and successfully tried to choreograph dances for women.